Theoretical prediction and analysis of hybrid material hat-shaped tubes with strengthened corner structures under quasi-static axial loading. (1st March 2021) - Du, Zhanpeng; Duan, Libin; Cheng, Aiguo; Wei, Baolv; Zhang, Guangya
Graphical abstract: Highlights: A new hat-shaped tube with strengthened corner structure is proposed. The theoretical prediction formulas of MCF for HMHT-SCS are given. A detailed discussion for HMHT-SCS and traditional hat-shaped structures is made. Abstract: This paper proposes an innovative hybrid material hat-shaped tube with strengthened corner structures (HMHT-SCS) to overcome the disadvantages of the limited energy absorption capacity and lightweight potential of conventional hat-shaped tubes. First, an improved theoretical prediction model of a corner element is established by modifying the simplified super folding element theory, and analytical formulas for energy absorption are derived under quasi-static axial loading. Second, a prediction model of the HMHT-SCS is developed based on the improved prediction model of corner element. Analytical formulas for the mean crushing force (MCF) of single-hat HMHT-SCS and double-hat HMHT-SCS are derived. Then, the accuracy of the analytical formulas is validated through axial crushing tests and simulation analysis. Finally, a discussion is performed. The total effect generation method is proposed to visually characterise the effects of input parameters on output responses. The parametric study showed that the thickness of the hat element of HMHT-SCS has the strongest effect on the MCF, and the thickness and material type of the hat element have similar effects on mass. The thickness of the corner element has a noticeable effect on MCF, while its section width has the weakest effect on the MCF and mass. Furthermore, the comparative analysis showed that the specific energy absorption (SEA) of the HMHT-SCS is larger than that of conventional hat-shaped tubes with one single material. Additionally, the SEA of the 'aluminium & steel' HMHT-SCS is larger than that of the 'steel & aluminium' HMHT-SCS under the same flow stress.